Croatian web text summarizer (CroWebSum) - Mikelić Preradović, Nives; Boras, Damir; Ljubešić, Nikola, informatičar (2010)
The paper describes automatic summarization of newspaper texts in Croatian language. The goal of the CroWebSum is to generate high-quality extracts that are both coherent and keep relevant information from the original text. The preliminary evaluation shows that extracts in the size of 10 % of the original text have good coherence, while the extract in the size of 5 % of the original text still conveys the most relevant information. Also, while cutting down news to SMS size (maximum 160 characters), CroWebSum performed quite well. The research brought us to conclusion that we should develop a technique that uses context vectors to calculate the semantic similarity between the terms in the document as well as pronoun resolution algorithm in order to improve the text summarization for Croatian language.
Projekt MZOS
Projekt MZOS
ENG